Home-based strength and balance exercises for fall prevention among older individuals of advanced age: a randomized controlled single-blind study - Jian Zhou; Bo Liu; Jian-fang Xu; Fu-bai-hui Wang; Hui Ye; Jin-Ping Duan; Xin-wen Cui (Annals of Medicine)
Objective This research was to explore the effectiveness, safety, and adherence of home-based strength and balance exercises for fall prevention among the self-reliant individuals of advanced age and analyzed the beneficial components.Method This randomized controlled single-blind study included 124 individuals aged 80 years and over(mean age 84.4±3.2 years). The test group (n=63) performed strength and balance exercises facilitated by sports video training (≥ 3 sessions a week, ≥ 30 minutes per session), while the control group (n=61) maintained their daily routines. We conducted a comprehensive geriatric assessment (self-care ability, muscle strength, mobility, cognition, and psychological status) at baseline and 12 months later and dynamic posture mapping for balance and gait.Results The test group had a decreased risk of falls compared to the control group (25.4%vs.44.3%, respectively; RR = 0.747; 95% CI: 0.551–0.975; p = 0.027). There was no statistically significant difference in the fall rate between the two groups (0.48 falls per person-year vs. 0.67 falls per person-year, respectively; IRR: 0.708; 95% CI: 0.394–1.275; p = 0.251). The composite equilibrium score (SOTcom) for vestibular and integrated balance on the Sensory Organization Test (SOT) increased in the test group, while SOTcom decreased in the control group. In the test group, there was a significant improvement in the indexes pertaining to response time, movement speed, directional control, and endpoint offset in some directions. Adherence was better in the test group, with 54.0% exercised ≥ 3 times per week and 28.6% exercised 1–2 times per week on average.Conclusion Home-based strength and balance exercises improved balance and reduced the risk of falls among the individuals of advanced age. The video-guided, remotely monitored regimen demonstrated effectiveness, safety, and compliance, although scope for improvement remains.